Pengembangan Media Pembelajaran Berbasis Video Animasi Menggunakan Aplikasi Powtoon Terhadap Motivasi Belajar Anak Usia Dini - Rika Irmadiyah; Chitra Charisma Islami (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
This study aims to develop animated video-based learning media using the powtoon application on early childhood learning motivation, and to determine the effectiveness of the media. This research is research and development or Research and Development (R&D). This research method uses the Borg & Gall research and development method in Sugiyono which is limited to 6 stages, namely potential and problems, data collection, product design, design validation, design improvement, and product testing. The results of the assessment carried out are the validity, practicality and effectiveness of the learning videos. The results of the validity assessment were media experts with an average of 85% and material experts with an average of 86.66%. The results of the teacher's response questionnaire practicality assessment with an average result of 93.3%, all three were in the Very Eligible category. Furthermore, the results of evaluating the effectiveness of learning videos on children's learning motivation have increased. From the percentage rate of 40.23% in the less effective category before using the media and becoming the effective category, namely at the percentage rate of 72.35% after using the media.